Waterbird richness in altiplano wetlands of northwestern Argentina - Caziani, Sandra Monica (2001)
We measured waterbird richness and abundance, and characterized wetland features (altitude, size, and presence of submergent vegetation) of 50 altiplano wetlands, during summer and winter, 1998. We estimated 36,700 individuals of 24 avian species during the summer census. James' Flamingo (Phoenicoparrus jamesi) and Andean Flamingo (P. andinus) were the most abundant species, followed by Horned Coot (Fulica cornuta), Chilean Flamingo (Phoenicopterus chilensis), and Crested Duck (Anas specularioides). These species comprised 78% of total individuals. In winter, we counted 7,421 individuals of 16 species, and the three flamingo species were the most abundant. In summer, we found Chilean and Andean Flamingos primarily in intermediate-altitude wetlands (3,500-4,000 m a.s.1.), whereas James' Flamingos and other waterbirds were above 4,000 m. In winter, the three flamingo species moved to lower-altitude wetlands (below 3,500 m). Waterbird abundance was positively correlated with wetland size in wetlands with aquatic vegetation, with waterbird richness in wetlands without macrophytes. During summer, total abundance and richness were significantly higher in wetlands with macrophytes, where Chilean Flamingo and ten other waterbird species (e.g., ducks, grebes, gulls, and coots) were more common. James' Flamingo was the only species more abundant in hypersaline wetlands. In summer, four wetlands (Grande, La Alumbrera, Vilama, and Pozuelos) contained 68% of the total individuals, with more than 3,000 waterbirds each. In winter, wetlands Pozuelos and Guayatayoc included 50% of waterbirds counted, with more than 5,000 birds each. Thirty four percent of the wetlands surveyed are within protected areas, but only in Laguna de los Pozuelos Natural Monument is it actually implemented. In 42% of the wetlands we detected land uses that could represent threats to these environments. Here we propose some criteria to detect and prioritize relevant sites for conservation of altiplano waterbirds: a) large aggregations of individuals, either seasonal or permanent, b) vulnerable and/or endemic species and presence of nesting sites, c) ecological uniqueness, d) proximity to other complementary wetlands, e) high heterogeneity between and within sites. The complementary use of these environments by waterbirds, both seasonally and spatially, suggests considering conservation action from a landscape perspective.